2021
DOI: 10.1038/s41467-021-27620-x
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphatase 2A inactivation induces microsatellite instability, neoantigen production and immune response

Abstract: Microsatellite-instable (MSI), a predictive biomarker for immune checkpoint blockade (ICB) response, is caused by mismatch repair deficiency (MMRd) that occurs through genetic or epigenetic silencing of MMR genes. Here, we report a mechanism of MMRd and demonstrate that protein phosphatase 2A (PP2A) deletion or inactivation converts cold microsatellite-stable (MSS) into MSI tumours through two orthogonal pathways: (i) by increasing retinoblastoma protein phosphorylation that leads to E2F and DNMT3A/3B expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 68 publications
0
29
0
Order By: Relevance
“… 302 , 303 Inhibition of PP2A with LB-100 has been reported to synergize with PD-1 to enhance the reactivity of microstatellite instability colon cancer to immunotherapy. 304 …”
Section: Progress In Innovative Pharmacological Approaches That Targe...mentioning
confidence: 99%
“… 302 , 303 Inhibition of PP2A with LB-100 has been reported to synergize with PD-1 to enhance the reactivity of microstatellite instability colon cancer to immunotherapy. 304 …”
Section: Progress In Innovative Pharmacological Approaches That Targe...mentioning
confidence: 99%
“…Mutations in either gene lead to high-frequency microsatellite instability (MSI) 54 . Yen et al 25 found that deletion of the Ppp2r1a gene, which encodes PP2A-A, in murine Lgr5 + intestinal crypt cells in vitro leads to MMR-deficient genetic signatures and positive MSI assay results. These findings have been corroborated in humans: CRC data from The Cancer Genome Atlas Project has revealed that MSI is associated with diminished mRNA and protein levels of PPP2R1A 25 .…”
Section: Lb100: a Modulator Of Immunotherapymentioning
confidence: 99%
“…Yen et al 25 found that deletion of the Ppp2r1a gene, which encodes PP2A-A, in murine Lgr5 + intestinal crypt cells in vitro leads to MMR-deficient genetic signatures and positive MSI assay results. These findings have been corroborated in humans: CRC data from The Cancer Genome Atlas Project has revealed that MSI is associated with diminished mRNA and protein levels of PPP2R1A 25 . These data suggest that PP2A plays a role in maintaining normal MMR, and aberrant regulation of PP2A is associated with MSI.…”
Section: Lb100: a Modulator Of Immunotherapymentioning
confidence: 99%
See 2 more Smart Citations